Effect of Marangoni condensation on the heat transfer performance of two-phase closed thermosyphons - Seo, Donghyun; Seo, Jin Hyeuk; Shim, Jaehwan; Nam, Youngsuk; Lee, Jungho (International Journal of Heat and Mass Transfer, 2023)
A two-phase closed thermosyphon (TPCT) is a heat pipe that effectively transfers heat through a phase change of the working fluid. In the evaporator, the working fluid evaporates and boils, the vaporized fluid is condensed, and the liquid condensate is resupplied by gravity to the evaporator. The thermal performance of the TPCT can be improved by enhancing the heat-transfer ability of the evaporator and condenser. Various studies have been conducted to improve the heat-transfer performance using nanofluids and surface modifications in the TPCT. However, these methods still have durability and economic feasibility limitations. In this study, the Marangoni effect was applied to the TPCT to improve condensation heat transfer by promoting pseudo-dropwise condensation to overcome the limitations of previous studies. Experiments were conducted by changing the ethanol fraction from 0% to 5% with deionized water and filling ratio from 25% to 75%. The results confirmed that the highest condensation heat transfer coefficient (∼45 kW/m2·K) was obtained at a filling ratio of 38% and an ethanol volume fraction of 0.075%, which was approximately 4 times greater than the TPCT with the same filling ratio without ethanol. It was confirmed that the Marangoni effect could improve the thermal performance of the TPCT, and it is expected that this work can be utilized in various TPCT-based applications.
Keywords: Condensation heat transfer; Dropwise condensation; Dropwise condensation heat transfer; Filling ratio; Heat transfer performance; Marangoni condensation; Marangoni effects; Thermal Performance; Two-phase closed thermosyphon; Working fluid; Dropwise condensation heat transfer; Heat pipe; Marangoni condensation; Thermal resistance; Two-phase closed thermosyphon(TPCT)